2012
DOI: 10.1016/j.virusres.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

USP18 restricts PRRSV growth through alteration of nuclear translocation of NF-κB p65 and p50 in MARC-145 cells

Abstract: Although the functions of porcine respiratory and reproductive syndrome virus (PRRSV) proteins are increasingly understood, the roles of host factors in modifying infection are less well understood. Growing evidence places deubiquitination at the core of a multitude of regulatory processes, ranging from cell growth to innate immune response and health, such as cancer, degenerative and infectious diseases. This report provides further information on the functional role of the porcine ubiquitin-specific peptidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…As a very successful virus, PRRSV has devastated the swine industry worldwide for nearly 30 years and has shown no sign of slowing down (38). Recent efforts have aimed at identifying anti-PRRSV host restriction factors and further characterizing their mechanisms of action (39)(40)(41)(42)(43)(44). In this study, we demonstrated that CH25H can inhibit PRRSV infection by producing 25HC, a mechanism similar to that reported previously for other viruses.…”
Section: Discussionsupporting
confidence: 81%
“…As a very successful virus, PRRSV has devastated the swine industry worldwide for nearly 30 years and has shown no sign of slowing down (38). Recent efforts have aimed at identifying anti-PRRSV host restriction factors and further characterizing their mechanisms of action (39)(40)(41)(42)(43)(44). In this study, we demonstrated that CH25H can inhibit PRRSV infection by producing 25HC, a mechanism similar to that reported previously for other viruses.…”
Section: Discussionsupporting
confidence: 81%
“…59 Additional in vitro studies found that the growth of PRRSV is restricted in Usp18-overexpressed MARC-145 cells. 51,60 This restriction is due to increased nuclear translocation of transcription factor p65 and decreased nuclear translocation of p50. 60 An in vivo study found that Usp18-deficient mice exhibit less replication of various viruses, including LCMV 15 and VSV.…”
Section: Role Of Usp18 During Viral Infectionmentioning
confidence: 99%
“…51,60 This restriction is due to increased nuclear translocation of transcription factor p65 and decreased nuclear translocation of p50. 60 An in vivo study found that Usp18-deficient mice exhibit less replication of various viruses, including LCMV 15 and VSV. 14 The antiviral effect is not due to enhanced ISGylation of ISG15 in the absence of USP18, because Isg15-deficient mice do not exhibit any antiviral impairment after infection with LCMV or VSV.…”
Section: Role Of Usp18 During Viral Infectionmentioning
confidence: 99%
“…The ubiquitin-specific peptidase 18 (USP18) as a host restriction factor restricts PRRSV growth through alteration of nuclear translocation of NF-κB p65 and p50 in MARC-145 cells (Xu et al, 2012). The tripartite motif (TRIM) family proteins make up the largest group of RING domain-containing E3 ligases.…”
Section: Other Cellular Pathways Involved In Prrsv Proliferationmentioning
confidence: 99%